NADPH Oxidase (Rboh) Activity is Up Regulated during Sweet Pepper (Capsicum annuum L.) Fruit Ripening - Ángela Chu-Puga; Salvador González-Gordo; Marta Rodríguez-Ruiz; José M. Palma; Francisco J. Corpas (MDPI AG, 2019)
In plants, NADPH oxidase (NOX) is also known as a respiratory burst oxidase homolog (Rboh). This highly important enzyme, one of the main enzymatic sources of superoxide radicals (O2•−), is involved in the metabolism of reactive oxygen and nitrogen species (ROS and RNS), which is active in the non-climacteric pepper (Capsicum annuum L.) fruit. We used sweet pepper fruits at two ripening stages (green and red) to biochemically analyze the O2•−-generating Rboh activity and the number of isozymes during this physiological process. Malondialdehyde (MDA) content, an oxidative stress marker, was also assayed as an index of lipid peroxidation. In red fruits, MDA was observed to increase 2-fold accompanied by a 5.3-fold increase in total Rboh activity. Using in-gel assays of Rboh activity, we identified a total of seven CaRboh isozymes (I–VII) which were differentially modulated during ripening. CaRboh-III and CaRboh-I were the most prominent isozymes in green and red fruits, respectively. An in vitro assay showed that CaRboh activity is inhibited in the presence of nitric oxide (NO) donors, peroxynitrite (ONOO−) and glutathione (GSH), suggesting that CaRboh can undergo S-nitrosation, Tyr-nitration, and glutathionylation, respectively. In summary, this study provides a basic biochemical characterization of CaRboh activity in pepper fruits and indicates that this O2•−-generating Rboh is involved in nitro-oxidative stress associated with sweet pepper fruit ripening.